Features of the deep structure of the Greenland territory near the Maniitsoq structure location - Yakymchuk, M.A.; Korchagin, I.M. (Reports of the National Academy of Sciences of Ukraine, 2021)
The results of experimental studies within the Maniitsoq structure in the south-western Greenland, as well as in the areas adjacent to it, are presented. Reconnaissance studies using the frequency-resonance methods of satellite images and photo images processing were carried out in order to confirm the endogenous (nonimpact) nature of the Maniitsoq structure, established by the results of geological and geochemical studies. In the course of processing, a satellite image of structure’s location, a volcanic complex with a root at a depth of 723 km, filled with ultramafic rocks, was discovered within it, which is an additional argument in favor of the endogenous nature of its origin. The position of the root of the volcano at a depth of 723 km indicates the ancient age of the structure. A basalt volcano with a root at a depth of 99 km and an upper boundary at a depth of 15 m was discovered in the surveyed hydrogen degassing area located next to the Maniitsoq structure. Responses at hydrogen frequencies from basalts began to be recorded from 25 m, and living water from 33 m. Results of site surveys indicate the advisability of conducting detailed studies within it in order to assess the prospects for organizing activities for the extraction of natural hydrogen, as well as hydrogen-enriched (healing) water. Within the three surveyed areas, the presence of volcanoes filled with ultramafic rocks was established, and signals were recorded at the frequencies of industrial micro-diamonds - lonsdaleites. In view of the fact that the responses at the lonsdaleite frequencies are recorded in almost every case of recording the signal from ultramafic rocks, it can be concluded that conditions are created in the volcanoes of ultramafic rocks for the synthesis of lonsdaleite in the deep intervals of the cross-section. The processing of a satellite image of the southern part of Greenland revealed volcanic structures with roots at a depth of 99 km, filled with dolomites and marls, as well as a volcano of siliceous rocks with a root at a depth of 723 km. The discovery during the reconnaissance studies of numerous volcanic complexes, filled with sedimentary, metamorphic, and igneous rocks of various compositions, can be considered an important argument in favor of the volcanic model of the formation of the external appearance of the Earth planet, as well as mineral deposits. The results of the work carried out indicate that the mobile direct-prospecting technology of frequency-resonance processing of satellite images and photo images can be used to study the deep structure and to determine (establish) the genesis of ring structures, study of volcanic complexes of various types, as well as search for combustible and ore minerals in various regions of the globe.